Peptide hydrolases in cotyledons of germinating lupin - Duarte de Almeida, I.; Ricardo, C. P. P.; Duque-Magalhães, M. C. (Phytochemistry, 1993)
Aminopeptidase (AP), carboxypeptidase (CP) and endopeptidase (EP) activities have been analysed in extracts prepared from cotyledons of dry and five and 14 days-germinated lupin seeds (Lupinus albus). At these three stages the pattern of the enzymatic activities change in a complex manner. In cotyledons germinated for five days, seven molecular forms of AP were present, which fall into four groups according to their substrate specificity and sensitivity to effectors. They represent a maximal complexity in relation to the AP pattern of the dry seeds or the 14 days-germinated cotyledons. The CP pattern increases in complexity from dry seeds to cotyledons germinated for 14 days, which showed a total of four isoenzymes. A number of EP activities of yet unknown specificity towards natural substrates were found in the cotyledons at the dry seed stage. The exopeptidases (APs and CPs) were expressed early. They increased rapidly up to day 5 and tended to stabilize or decline afterwards, while the EPs had a very small activity in dry seeds and increased throughout the 14 day period.